Implementation of Marketing Strategies Using the SWOT Method In an Effort to Increase Competitiveness in Ginastel Iced Tea Sales - Lembayung, Wartopo Eksa; Asmawan, Mohammad Chairil (Jurnal Dakwah dan Komunikasi, 2025)
This research was carried out with the aim of understanding the marketing strategy used by Ginastel Ice Tea, Sukoharjo Regency. This research adopted a descriptive qualitative approach as a methodology and used in-depth interviews. The research location included Ginastel Ice Tea, Sukoharjo Regency, and participants involved owners, employees and consumers from that branch. The data analysis approach applied in this research is SWOT analysis. The results of research for business development on Ginastel Ice Tea are grouped into 4 categories, namely: (1) SO Strategy Maintaining price and product quality to increase consumer loyalty Establishing mutually beneficial cooperation to expand the marketing area (2) WO Strategy Expanding the marketing area so that consumers can easily reach a product (3) ST Strategy Continuously innovates in various flavor variants to increase the competitiveness of a product, and (4) WT Strategy Utilizes various promotional media to attract consumers by increasing and expanding promotion of a product. The next research focuses on the digital marketing strategy of the Ginastel iced tea business.